Identifikasi Risiko Ergonomi dan Intervensi Berbasis K3 pada Pekerja Bank: Sebuah Model Praktis untuk Pencegahan Ergonomi di Lingkungan Kerja Perkantoran - Andi Nadya Eka Putri; Nadia Muthia Hanifah Amrin; Muhammad Evendi Halulanga (PT.Mantaya Idea Batara, 2026)
Background: Banking employees are commonly exposed to hidden ergonomic hazards resulting from prolonged sitting, repetitive movements, and extensive computer use. These exposures contribute to musculoskeletal disorders (MSDs) and visual fatigue, posing risks to occupational health and productivity. Methods: A community-based intervention was conducted on 4 October 2025 at Bank in Makassar City, involving 20 participants. An andragogical training model was implemented through lectures, discussions, risk identification sessions, and hands-on demonstrations on workstation adjustment and micro-break techniques. Ergonomic complaints were qualitatively identified, and risk factors were mapped based on established ergonomic frameworks. Participants reported prevalent ergonomic-related symptoms, especially low back pain, neck–shoulder discomfort, and visual fatigue. Identified risk factors included static sitting postures, repetitive hand wrist movements, and suboptimal workstation design. The training improved participants' understanding of ergonomic risk factors and introduced practical OSH-based strategies, including workstation redesign, micro-break application, and posture correction. Result: These results align with global evidence on high MSDs prevalence among office and banking workers. Banking employees are at considerable risk of MSDs and visual strain due to prolonged computer use and poor workstation ergonomics. Conclusion: OSH-based ergonomic interventions, particularly engineering and administrative controls, are essential for reducing exposure and protecting worker health. Strengthened management commitment and ongoing ergonomic training are key to sustaining safe, productive banking environments.